Right heart catheterization procedures in patients with suspicion of pulmonary hypertension – experiences of a tertiary center - Grymuza, Maciej; Małaczyńska-Rajpold, Katarzyna; Jankiewicz, Stanisław; Siniawski, Andrzej; Grygier, Marek; Mitkowski, Przemysław; Kałużna-Oleksy, Marta; Lesiak, Maciej; Mularek-Kubzdela, Tatiana; Araszkiewicz, Aleksander (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction : Right heart catheterization (RHC) is an invasive procedure providing direct and accurate measurements of hemodynamics of the cardiovascular system. Acute pulmonary vasoreactivity testing (APVT) following basal RHC in some patients is an established tool evaluating the reversibility of hypertension in the pulmonary vasculature. Aim : We sought to assess the most common indications, vascular approaches and complications during RHC in a single high-volume center. Material and methods : A total of 534 RHC procedures in 348 patients (64% male) were performed. The prospective registry was carried out for 28 months. Collected data included indications for RHC, vascular approaches, hemodynamic and clinical data, complications and response of pulmonary vessels in APVT. Results : In 401 (75%) procedures pulmonary hypertension (mean pulmonary artery pressure (mPAP) ≥ 25 mm Hg) was confirmed. Left heart failure was the most common indication (55.8%), mainly ischemic (26%) or dilated cardiomyopathy (19.9%). Other indications included a suspicion of arterial (21.7%), or chronic thromboembolic pulmonary hypertension (14.6%). The right internal jugular vein approach was used in 89.1% of procedures. Acute pulmonary vasoreactivity testing was performed in 143 patients, and it was positive in 67 (46.9%) cases. Complications occurred in 21 (3.9%) procedures and included pulmonary edema (0.2%), pneumothorax (0.2%) and puncture of the artery followed by the insertion of a vascular sheath (0.4%), atrial arrhythmia (0.2%), superior vena cava dissection (0.2%), incidental artery puncture (1.1%) and local hematoma (2.2%). Conclusions : The most frequent indication for RHC was left heart failure, and the most common approach was the right internal jugular vein. RHC is safe procedure with a low rate of major complications.